Allelopathic potential of paddy field weeds on the growth of Cicer arietinum L. - P. Elavazhagan; A. K. Rajalakshmi (Innovations in Agriculture)
A study was conducted to investigate the allelopathic potential of aqueous whole plant extracts of Ammannia baccifera L., Eclipta alba (L.) Hassk. and Cyperus difformis L. on germination and growth of Cicer arietinum L. plants. Different concentrations (10%, 15%, 20% and 25%) of whole plant extracts were prepared from three weed species. Experiments were conducted by petri plate culture. The germination percentage, root and shoot length, fresh and dry weight were adversely inhibited by Cicer arietinum L. seedlings with increasing the concentration of weed extract. From the study of result, Ammannia baccifera L. was high toxic and Cyperus difformis L. was less toxic to the germination and seedling growth of test crop.